EVALUATION OF THE ANTIFUNGAL ACTIVITIES OF THREE ESSENTIAL OIL COMPONENTS AGAINST PENICILLIUM EXPANSUM SPORES - Hassan, Barkai; Soumya, Elabed; Sanae, Guissi; Saad, Ibnsouda Koraichi (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The aim of the present study was to evaluate the antifungal potential of Î²-Ionone; carvone and 1,8-cineole which are three essential oil components. Methods: For that purpose, the minimum inhibitory (MIC) and fungicidal (MFC) concentrations of these compounds were determined by the microdilution method using the 96 well microtiter plates. The efficiency of these compounds was tested against the spores of Penicillium expansum; a strain responsible for huge post-harvest losses during storage of fruits and capable of producing patulin, a very dangerous mycotoxin for the human health. Results: The obtained results showed a very strong inhibition of the growth of P. expansum spores with very low MIC values determined for Î²-Ionone (0.625 %); Carvone (0.3125 %) and 1,8-cineol (0.078125 %). In addition, the evaluation of MFCs for the tested essential oil components showed that Î²-Ionone and carvone molecules exhibited the same MFCs at 5 % against P. expansum spores. However, the best fungicidal activity was found with the 1,8-cineole molecule at a concentration of 1.25 % vis-Ã -vis of the spores of this strain. Conclusion: This study, which shows for the first time the antifungal potential of these three molecules against this strain, also allows to highlight the possibility of using these essential oil compounds in the formulation of commercial antifungal products.